ULTRAVIOLET DOOR’S SEBAGAI DESINFEKTAN PADA PINTU KELAS UNTUK MENCEGAH PENYEBARAN VIRUS COVID-19 - Dina Afkarina; Sudarti (Poltekkes Kemenkes Surabaya, 2022)
The Covid-19 virus (SARS Cov-2) is dangerous for humans because it can infect the respiratory tract. Currently, the case of the corona virus in Indonesia is indeed decreasing, so many activities can be carried out as usual, one of which is activities in the world of lectures. However, health protocols must still be adhered to so that the corona virus does not spread again. In addition to implementing health protocols, UV light devices can also be developed to sterilize classrooms from the corona virus. The purpose of this study was to design ultraviolet door's as a disinfectant on classroom doors to prevent the spread of the covid-19 virus. The method used in this research is a literature review or literature study. This study illustrates that UV light sterilization devices in the form of ultraviolet door's can be used as a disinfectant to prevent the spread of the covid-19 virus. This research is expected to be an innovation for students to design ultraviolet door's to prevent the spread of the covid-19 virus.